Development of Differentiate Student Worksheets: an Efforts to Improve Student Argumentation Ability - Putra, Zuhadur Ra'is Ariyono; Rahardi, Rustanto; Sisworo, Sisworo (Universitas Muhammadiyah Mataram, 2024)
Online learning experiences have been associated with reduced learning outcomes and limited student engagement in argumentation. To address this issue, the focus on teaching materials becomes crucial, especially in promoting differentiated learning to accommodate pandemic-induced learning losses. A prime candidate for enhancing argumentation skills is the study of quadrilaterals within mathematics. Mastering the quadrilateral concept and its argumentative structure is pivotal for students. Hence, the creation of student worksheets employing differentiated learning principles is imperative. This research aims to develop valid, practical, and effective quadrilateral worksheets with a focus on adversity quotient differentiation. The ADDIE model guides the development process through Analysis, Design, Development, Implementation, and Evaluation stages. Rigorous evaluation, including expert validation (83.8% very valid), field trials (91% very practical), and N-Gain score analysis (0.73, indicating effectiveness), underscores the quality of the developed worksheets. In conclusion, the adversity quotient differentiated quadrilateral worksheets has been successfully crafted to enhance students' argumentation skills. It is deemed valid, practical, and effective in improving learning outcomes. This initiative holds potential for addressing the challenges posed by online learning and contributes to students' academic development.